Effect of Heat Treatment Parameters on Microstructure and Mechanical Properties of (AISI1005) Steel (University of Thi-Qar Journal for Engineering Sciences, 2016)
This study aims to investigate tensile properties and work hardening behavior of dual phase (DP) steels. A series of DP steels containing ferrite and martensite with different volume fractions of martensite (Vm) were produced by intercritical heat treatment. Microstructural investigations, hardness test, and tensile test were carried out. The experimental results showed that dual phase steels at 760oc and10s have excellent mechanical properties in terms of tensile strength, ductility and fracture energy. A further increase in Vm was found to increase tensile strengths and ductility. The increasing and then decreasing trend in tensile strength is in contrast to the law of mixture. These unusual behaviors are discussed and explained. Work hardening behavior was analyzed in terms of Holloman analysis.